Can Our Service Change Us? Bringing the Classroom to Service Learning in the Southern African Kingdom of Lesotho - Scott Rosenberg (The University of Alabama, 2022)
Based on a decade's worth of service-learning trips to Lesotho, this paper focuses on the role of nightly discussion sessions in achieving our learning goals. It also examines how we carried out our community-service projects in conjunction with class material to help students move past negative stereotypes and objectification of the Basotho (an ethnic group whose ancestors have lived in southern Africa since around the fifth century) toward a greater understanding of the Basotho as people. During our community service, students often expressed feelings of pity for the Basotho as well as a sense of frustration at why they do not do more to help themselves. This paper will also address how the trip helps students move from feelings of pity to that of empathy, as well as creating an environment that helps break down the barriers between those performing community service and the communities they are working with.